(untitled) (Research, Society and Development, 2022)
The research aimed to reflect on pedagogical practices in the playful perspective of Montessori and Pikler, the choice of theme was due to the context of the application of play in remote classes established during the pandemic. time the child was misunderstood in the development of autonomy, considering the need for education and knowledge in early childhood unnecessary. This study is a literature review with a qualitative approach focusing on the phenomenon itself and it is not expected that graphs or statistical indices will be generated. The theoretical foundation of this study used, as research means, scientific articles, search sites and repositories such as Scielo, texts by theorists and scholars who discuss the subject, as well as official documents from the Ministry of Education (MEC), such as the Law of Guidelines and Bases (LDB) (BRASIL, 1996) and the National Curricular Common Base (BNCC) (BRASIL, 2018). The research study developed in this bibliographic review, in addition to allowing us to know play as an incentive in the learning of children in early childhood education, from the perspective of Montessori and Pikler’s methods, also provokes reflection on the performance of early childhood education professionals in the face of games. inside the classroom. Because it is not just a form of recreation, but a means for learning.